Multifunctional roles of insulin-like growth factor binding protein 5 in breast cancer - AKKİPRİK, MUSTAFA; ÖZER, SIDIKA AYŞE (BMC, 2008)
The insulin-like growth factor axis, which has been shown to protect cells from apoptosis, plays an essential role in normal cell physiology and in cancer development. The family of insulin-like growth factor binding proteins (IGFBPs) has been shown to have a diverse spectrum of functions in cell growth, death, motility, and tissue remodeling. Among the six IGFBP family members, IGFBP-5 has recently been shown to play an important role in the biology of breast cancer, especially in breast cancer metastasis

however, the exact mechanisms of action remain obscure and sometimes paradoxical. An in-depth understanding of IGFBP-5 would shed light on its potential role as a target for breast cancer therapeutics.
Keywords: FACTOR BINDING-PROTEIN-5 GENE; MAMMARY-GLAND INVOLUTION; ACID-LABILE SUBUNIT; OSTEOBLAST CELL-PROLIFERATION; IGF-I BINDING; NEUROBLASTOMA-CELLS; EPITHELIAL-CELLS; RETINOIC ACID; CARCINOMA CELLS; FACTOR (IGF)-I